Impact of lecture hall’s background noise on undergraduates’ higher order thinking skills: A field study - Nada Atef; Yasser Mansour; Hanan Sabry (Ain Shams Engineering Journal)
Mastering higher-order thinking skills in Higher Education Institutions has become a must for undergraduates to cope with the continuously changing world and the vast globalization around them. Acoustics is recognized as a vital indoor environmental quality aspect having a significant impact over the learning performance of students inside learning spaces whether classrooms or large lecture halls. The quality of education of an institution is measured by its learning efficiency. Noise is a main parameter of classroom acoustics, it is considered a primary cause of annoyance, disturbance, and stress among students of all ages. A considerable number of studies have examined the impact of background noise on school students’ learning efficiency; thus, assessing lower order thinking skills. The majority of research studies have examined the same impact on university students, however, most of the studies using task tests as an assessment approach only assess reading, writing, math, and memory tests. This research is a field study aimed at evaluating the impact of lecture hall background noise over undergraduates’ higher-order thinking skills. The study has assessed three higher-order thinking skills including critical thinking, analytical thinking, and creative thinking under three different acoustic conditions representing the quiet, comfortable, and noisy lecture hall. Higher-order thinking skills were assessed by applying standard assessment scales. The study was conducted in a uniform lecture hall inside the architecture department building at the Faculty of Engineering, Ain Shams University in Egypt with a total sample of 90 architecture students. The results have revealed that no significant interaction effect was found between background noise and gender while low background noise had a statistically significant effect on the creative thinking scores compared to the moderate and high background noise levels.